2010
DOI: 10.1007/s11605-009-1121-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Imatinib Resistance Associated with Downregulation of C-Kit Expression in Recurrent Gastrointestinal Stromal Tumor (GIST): Optimal Timing of Resection

Abstract: Continued monitoring by a multidisciplinary team, including a surgeon, is vital for the success of neoadjuvant imatinib therapy for unresectable primary or recurrent GIST in the context of emergence of secondary resistance. As such, surgeons should participate in managing imatinib-treated GIST, as resection may become a viable curative option. This case also highlights that major oncologic resections can be safely performed in older persons when their performance status and comorbidities are carefully consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Matrix metalloproteinases, particularly MMP1, actively shape the stromal microenvironment during sarcoma development 76 – 78 . In fact, a recent study reported that chondrosarcoma cell invasion correlates with MMP1 expression in tumor cells and that a transient downregulation of MMP1 expression decreases invasion in vitro 79 , 80 . In our recent study, we found that GIST cells not only constitutively released low levels of MMP1, but that challenging myometrial smooth muscle cells with GIST patient-derived exosomes (but not exosomes from healthy donors) significantly increased MMP1 production, which in turn enhanced GIST cell invasion 81 .…”
Section: Gist Tumor Microenvironment and Tumor-derived Exosomesmentioning
confidence: 59%
See 1 more Smart Citation
“…Matrix metalloproteinases, particularly MMP1, actively shape the stromal microenvironment during sarcoma development 76 – 78 . In fact, a recent study reported that chondrosarcoma cell invasion correlates with MMP1 expression in tumor cells and that a transient downregulation of MMP1 expression decreases invasion in vitro 79 , 80 . In our recent study, we found that GIST cells not only constitutively released low levels of MMP1, but that challenging myometrial smooth muscle cells with GIST patient-derived exosomes (but not exosomes from healthy donors) significantly increased MMP1 production, which in turn enhanced GIST cell invasion 81 .…”
Section: Gist Tumor Microenvironment and Tumor-derived Exosomesmentioning
confidence: 59%
“…In particular, in vivo-derived exosomes appeared to be a potent exogenous source of MMP induction in stromal cells, which in turn acted as a pro-invasion factor for GIST cells. It is known that tumor cells acquire some of the required properties for growth and invasion by the specific modification of the tumor microenvironment 79 . However, due to the complex nature of these interactions, it is only by altering specific components of this network that it will be possible to identify molecules with pro-tumorigenic and anti-tumorigenic functions.…”
Section: Gist Tumor Microenvironment and Tumor-derived Exosomesmentioning
confidence: 99%
“…The role of preoperative imatinib for treating primary localized GIST is questionable, as there is no clear evidence on the role of preoperative imatinib to obtain R0 resection. It is believed that exposure to preoperative imatinib may lead to a downregulation of c-kit expression with consequently selection of imatinib resistant clones of cancer cells, which may preclude the benefit of the surgical resection and the adjuvant therapy [16]. The role of new drugs (sunitinib) is still under evaluation in patients with progressive disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the effect of preoperative application of imatinib mesylate in patients with primary GIST of different sites was examined. While some authors report tumor shrinkage in all patients with a median size reduction of 34% and conclude that, in unresectable or locally advanced GIST, preoperative imatinib mesylate can be useful to improve resectability and reduce surgical morbidity [84], others classify the response clinically into three groups: (1) early responders (up to 70% [80,85]), (2) those with stable disease, and (3) those with progressive disease while on targeted therapy [85]. The impact of preoperative imatinib therapy depends on the primary KIT and PDGFRA mutation status.…”
Section: Neoadjuvant Therapymentioning
confidence: 99%